2015
DOI: 10.15585/mmwr.mm6439a4
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of an Ebola Treatment Unit and Laboratory — Bombali District, Sierra Leone, July 2014–January 2015

Abstract: The first confirmed case of Ebola virus disease (Ebola) in Sierra Leone related to the ongoing epidemic in West Africa occurred in May 2014, and the outbreak quickly spread. To date, 8,704 Ebola cases and 3,955 Ebola deaths have been confirmed in Sierra Leone. The first Ebola treatment units (ETUs) in Sierra Leone were established in the eastern districts of Kenema and Kailahun, where the first Ebola cases were detected, and these districts were also the first to control the epidemic. By September and October … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 2 publications
0
12
0
Order By: Relevance
“…Participants in our study reported reluctance to call the national hotline if they had a fever because they were afraid they would not return alive. Participants reported seeing many deaths at the beginning of the epidemic which provided the rationale for these fears, as did the high Ebola-related fatality rate in 2014 in Sierra Leone [ 22 , 27 ]. Although Ebola treatment and surveillance capacity had increased greatly by the time of our research [ 6 ], participants’ early impressions likely remained salient in their attitudes towards accessing the response system.…”
Section: Discussionmentioning
confidence: 99%
“…Participants in our study reported reluctance to call the national hotline if they had a fever because they were afraid they would not return alive. Participants reported seeing many deaths at the beginning of the epidemic which provided the rationale for these fears, as did the high Ebola-related fatality rate in 2014 in Sierra Leone [ 22 , 27 ]. Although Ebola treatment and surveillance capacity had increased greatly by the time of our research [ 6 ], participants’ early impressions likely remained salient in their attitudes towards accessing the response system.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, very little transmission seemingly occurred between these two neighboring districts (Figure 2). Although the first laboratory confirmed case of EVD in Bombali was detected in July 2014, a dedicated laboratory and Ebola Treatment Unit was only established in the district in December 2014 [24]. Prior to this, patient samples were being tested by laboratories in other districts of SLE.…”
Section: Resultsmentioning
confidence: 99%
“…Like other infectious disease interventions, EVD outbreak interventions require efficiently designed and operated treatment facilities in order to ensure a low risk of nosocomial infection and easy to maintain monitoring WASH/IPC practices. [ 11 ] Our study highlights parameters that are key in designing and managing a treatment facility for future infectious disease outbreaks in resource-limited settings.…”
Section: Discussionmentioning
confidence: 99%